Implementasi Pendidikan Karakter Melalui Program Literasi Siswa di Sekolah SMP Negeri 2 Binjai Langkat - Rahmi Utami; Yholla Wilanda; Milfa Yetty; Muhamad Hamdan (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2025)
AbstractThe purpose of this study is to determine the implementation of character education for students through literacy programmes at SMP Negeri 2 Binjai Langkat, to identify the strategies used by teachers in implementing character education for students through literacy programmes, and to identify the obstacles faced by teachers in implementing character education for students through literacy programmes at the school. This research is a qualitative field study, which involves collecting data in the field. The research uses field research methods, including observation, interviews, and documentation. The results of this study indicate that character education is reflected in daily life at school, both by the principal, teachers, and students. Teachers' strategies in implementing character education for students through student literacy programmes at school include several methods, such as teachers always setting a good example and being role models for students, teachers always giving appreciation and moral messages, and teachers always guiding students to always be honest and open about things. Challenges teachers face in implementing character education through student literacy programmes include students often ignoring teachers when they provide motivation. Lack of motivation, both from within the students and from external sources, as well as students arriving late to school, are significant challenges for schools in beginning to change students' character.